Impact of deprivation of school physical space on child development during the pandemic: the perception of preschoolers’ families - Gabriela Gomes Prado de Almeida Vita; Tatiane Martins Jorge (Revista CEFAC, 2023)
ABSTRACT Purposes: to characterize the family and school contexts of children enrolled in nursery schools, preschools, or kindergartens in 2020, during the COVID-19 pandemic, and verify the effects of deprivation of school physical space on their development, in the perception of families regarding cognitive-linguistic, socioemotional, and motor aspects. Methods: the sample comprised 139 families of children aged 1 year to 5 years and 11 months, living in the state of São Paulo, Brazil, who answered an online questionnaire on the characterization of the family and school contexts and the impacts on cognitive-linguistic, socioemotional, and motor aspects. The study used the chi-square, Kruskal-Wallis, and Mann-Whitney statistical tests, with the significance set at p-values ≤ 5%. Results: older children were associated with being transferred to other schools (p = 0.0192) and greater socioemotional impairment (p = 0.0011). Smaller children felt fewer positive effects on the cognitive-linguistic aspect (p = 0.0137). The absence from the school environment and the overall effects of the pandemic negatively influenced them (p = 0.0404; p = 0.0134). Conclusion: the mean age of the parents/guardians was 36 years, with a Bachelor’s degree, and working from home. The children enrolled in public or private schools had online activities. All children were exposed to screens, most of them for 4 or more hours per day. The socioemotional aspect was the most impaired one, followed by the cognitive-linguistic aspect. The negative effects outweighed the positive ones.